2021
DOI: 10.1038/s41467-021-26734-6
|View full text |Cite
|
Sign up to set email alerts
|

String Phase in an Artificial Spin Ice

Abstract: One-dimensional strings of local excitations are a fascinating feature of the physical behavior of strongly correlated topological quantum matter. Here we study strings of local excitations in a classical system of interacting nanomagnets, the Santa Fe Ice geometry of artificial spin ice. We measured the moment configuration of the nanomagnets, both after annealing near the ferromagnetic Curie point and in a thermally dynamic state. While the Santa Fe Ice lattice structure is complex, we demonstrate that its d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…1, C and D. SFI lends itself to the study of topological kinetics because, as we previously showed ( 14 ), the lattice geometry forces unhappy vertices to form one-dimensional (1D) strings that can either end within interior plaquettes or form closed loops [( 16 ), section S3]. In Fig.…”
Section: Strings In Santa Fe Icementioning
confidence: 91%
See 3 more Smart Citations
“…1, C and D. SFI lends itself to the study of topological kinetics because, as we previously showed ( 14 ), the lattice geometry forces unhappy vertices to form one-dimensional (1D) strings that can either end within interior plaquettes or form closed loops [( 16 ), section S3]. In Fig.…”
Section: Strings In Santa Fe Icementioning
confidence: 91%
“…Such arrays, known broadly as artificial spin ice systems, have displayed a range of exotic collective phenomena and technological potential ( 11 , 12 ). The particular array geometry that we studied is Santa Fe ice (SFI) ( 13 , 14 ). The structure of SFI is shown in Fig.…”
Section: Strings In Santa Fe Icementioning
confidence: 99%
See 2 more Smart Citations
“…ML method 30 is a promising approach for alternatively dealing with a large fraction of data and sweeping over a huge design space, avoiding the rigorous requirements of the aforementioned conditions. For instance, by providing a tailored computational scheme, ML substantially accelerates the satisfactory prediction of mechanical properties and inverse design of metamaterials.…”
Section: Introductionmentioning
confidence: 99%